Abjad Numerals between Arabic and Hebrew, Models and Comparisons - Oudeh, Salameh Saleem; Hamed, Ahmed; Shaqour, Adel (Journal of Arabic Language Sciences and Literature, 2023)
The research aims to reveal abjad numerals or poetic history between Arabic and Hebrew, by comparing letters and numbers, focusing on camel arithmetic in the two languages, its continuity in Hebrew, its development until it became used in Hebrew in their lives until now, and the software that carried its idea in Hebrew, and numbering the chapters of the Torah and its parts, while in Arabic it became independent with its own numbers called the Arabic numerals, and it focused on the date of death in writing its prose and poetry, striving for accuracy in transmission and scrutiny in the historical novel.